Imago Dei, Ontological and Relational Interpretations. Introducing Edith Stein to the Debate - Christof Betschart (Warszawskie Studia Teologiczne)
The complex theological treatment of the person as imago Dei has focused on ontological, functional, relational or eschatological interpretations, which either belong or possibly belong to all human beings. It is however unusual to encounter a reflection on the person’s intrinsic uniqueness as imago Dei. For Edith Stein intrinsic or a priori individuality refers to a unique quality of the person’s soul which unfolds more or less fully in the unity of the person’s body-soul-spirit unity: «the soul is destined for eternal being, and this destination explains why the soul is called upon to be an image of God in a “wholly personal manner.”» (FEB 504 [422]) This ontological approach contributes to a consideration of interpersonal enrichment through love, as a way to personal fulfilment and to complementarity through communion. An ontological approach to personal individuality thus paradoxically leads to the discovery of the existential primacy of relationality.